Optimalisasi Kinerja Fresh Water Generator dalam Meningkatkan Destilasi di Kapal MT.Pangalengan - Komang Vivi Gayatri; Iksan Saifudin; Kris Wanto; Dedtri Anwar; Aris Jamaan (Politeknik Pelayaran Sulawesi Utara, 2024)
This machine Fresh Water Generator has The role is very important in the smooth operation of ships, where in the operation of ships insep``arable from the need for fresh water. This research aims to be able to find out the causes, impacts, and efforts that occur in fresh water generators so that they can increase the production of fresh water on board. The type of method used in this study is to use qualitative method , namely research that aims to solve the actual problems faced an collect data or information to be compiled,analyzed and analyzed later. Problems that often occure in Fresh Water Generator are the incompatibility of fresh air and sea air in each pipe,the temperature of fresh air and sea air which is not suitable before and after passing through a Fresh Water Generator, and the movement or water attached to the surface of the plate both in the evaporator and condenser arising from evaporation in the evaporator and condensation on the condenser.